Decoupling Relationship Between Water Resources Utilization and Economic Development in Henan Province Based on Water Footprint-Extended LMDI Model - LU Qiuyu (Renmin Zhujiang)
Aiming at the related problems of water resources constraining economic development in Henan Province,this paper constructs the water footprint-extended LMDI model,decomposes the decoupling driving factors into four decoupling factors,and studies the decoupling relationship between water resources utilization and economic development in Henan Province from 2004 to 2018.The results show that:In terms of the possession and self-sufficiency rate of total per capital water footprint,the overall water shortage in Henan Province has been alleviated,but it is still in a state of shortage;In terms of decoupling state,the overall decoupling of Henan Province is in a good statel,the decoupling state of agricultural water is relatively stable,and the hydrological year has an impact on the agricultural virtual water consumption and decoupling state;In terms of decoupling factor decomposition,the technological decoupling factor contributes to the decoupling in Henan Province,the industrial structure and scale economy are the main promoting and inhibiting factors of decoupling,respectively,and the change of population driving factor has no obvious inhibiting effect on decoupling in Henan Province.Therefore,it is necessary to improve the utilization efficiency of water resources,the repetition rate of industrial water use,and improve the agricultural irrigation water-saving technology in Henan Province.